THE COMBINATION OF INQUIRY, LEARNING COMMUNITY, AND TOTAL PHYSICAL RESPONSE: A STUDY ON DEVELOPING ENGLISH LANGUAGE SKILL FOR ELEMENTARY SCHOOL STUDENTS - Herwanis, Delfia; Sarinauli, Barep (Universitas Islam Negeri Alauddin Makassar, 2021)
The performance of the English language skill of the fifth graders of SD Negeri 1 Takengon was unsatisfactory (avarage score = 34). The limited achievement was due to ineffective teaching and learning process. Therefore, it was suggested that a specific treatment of learning process needs to be well performed. This study aims at finding out if the combination of the Inquiry, Learning Community, and Total Physical Response is able to develop the performance of the students’ English language skill. The study focuses on the students’ performance to verbally respond to any simple instruction with acceptable actions within the context of classroom and school environment; and verbally express any expression of the following speech acts as: giving examples to do something, gesticulation, and giving directions (Departemen Pendidikan Nasional, 2006). In terms of the speaking skill, this study just concentrates on pronunciation and comprehension aspects. To achieve the goal of the study, an experimental approach with the one-group pre-test and post test design was used. The sample for the treatment was 20 students out of 58 students population which was selected randomly. The result shows that the performance of the students’ English language skill in terms of comprehension and pronunciation was significantly improved (34 to 60). In conclusion, the research questions of this research are answerable—the combination of Inquiry, Learning Community, and Total Physical Response does lead to developing students’ English ability in responding to simple instructions, and in expressing such speech acts as giving examples to do something, gesticulation, and giving directions. The hypothesis (Ha) of this research is then accepted as it provides a positive impact for the development of the students’ English language ability, particulary in the area of focus of the study.